Building e-commerce systems using semantic application framework. (21st September 2004) - Li, Bing; Tsai, Wei-Tek; Zhang, Liang-Jie
This paper proposes a novel approach to implement automatic business process compositions (ABPC), which are based on the Semantic Application Framework (SAF) and the Semantic Application Template (SAT). To build an e-Commerce system using SAF, three problems need solving: developing a new semantic application, converting an existing application to a semantic application, and composing a new business process with existing semantic applications. The vocabulary-oriented business logic makes requirement specifications comparable. A business composer works over a distributed techniques independent platform and matches requirement specifications in SAT with SATs of existing legacy systems to construct a new business process.